2012
DOI: 10.1093/aje/kws404
|View full text |Cite
|
Sign up to set email alerts
|

Two Epstein-Barr Virus-Related Serologic Antibody Tests in Nasopharyngeal Carcinoma Screening: Results From the Initial Phase of a Cluster Randomized Controlled Trial in Southern China

Abstract: A nasopharyngeal carcinoma (NPC) mass screening trial using a combination of immunoglobulin A antibodies to Epstein-Barr virus capsid antigen and nuclear antigen-1 by enzyme-linked immunosorbent assay in addition to indirect mirror examination in the nasopharynx and/or lymphatic palpation (IMLP) was conducted in southern China. Cantonese aged 30-59 years residing in 2 cities randomly selected by cluster sampling, Sihui and Zhongshan, were invited to participate in this screening from May 2008 through May 2010.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
171
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(172 citation statements)
references
References 26 publications
0
171
0
1
Order By: Relevance
“…Our results that point to the utility of EBNA1 IgA antibody as a sensitive screening marker are further supported by large, ongoing NPC screening trials being conducted in China in areas with high endemic rates of NPC. [2327] The sensitivity of the EBNA1 IgA assay utilized in that setting to diagnose NPC within a year of screening approached 90% and illustrated application of this screening tool in a general population setting for identifying those most likely to be harboring prevalent NPC. [28] However, it should be noted that the performance characteristics of any EBNA1 IgA test differ if applied to detect prevalent NPC that will present clinically within the following year versus incident NPC that will develop and present over the course of five years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results that point to the utility of EBNA1 IgA antibody as a sensitive screening marker are further supported by large, ongoing NPC screening trials being conducted in China in areas with high endemic rates of NPC. [2327] The sensitivity of the EBNA1 IgA assay utilized in that setting to diagnose NPC within a year of screening approached 90% and illustrated application of this screening tool in a general population setting for identifying those most likely to be harboring prevalent NPC. [28] However, it should be noted that the performance characteristics of any EBNA1 IgA test differ if applied to detect prevalent NPC that will present clinically within the following year versus incident NPC that will develop and present over the course of five years.…”
Section: Discussionmentioning
confidence: 99%
“…[14] However, general population screening with EBNA1 IgA might be more feasible in high-risk areas such as the Guangdong province of China (NPC incidence = 50 × 10 5 ). [23] (Supplemental Table 1)…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed considerable heterogeneity in antibody responses to individual proteins in nasopharyngeal carcinoma patients, which suggested that single antibody detection is insufficient to meet the needs of nasopharyngeal carcinoma diagnosis and combined detection is necessary (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of antibodies against EBV in the lytic phase are important predictive markers for NPC risk (57). Recently, 2 EBV-related serologic antibody-based (EBV VCA/IgA and EBNA1/IgA) ELISA were used in the initial phase of a randomized trial in Southern China (67). EBV microRNAs, which are present at functional levels in NPC tissues and in serum of patients with NPC (68), could be developed as a quantitative serum-based screening assay for NPC in the future.…”
Section: Field and Laboratory Studies On Nasopharyngeal Carcinomamentioning
confidence: 99%